The revolution of 1917: the end of the epoch without continuation - Rafael S. Khakimov (Историческая этнология, 2017)
By the beginning of the 20th century, the time had come for Russia to say farewell to the Long Medieval period. Not only the Russians, but also many other peoples of the empire, including the Tatars, embarked on the path of capitalism. They demanded civil rights, freedom of speech, the state system reform, in particular, the transition to federal Russia. Among the causes of the 1917 revolution was the political culture which was being developed based on arbitrary decisions; serfdom that had been a powerful brake on the country's economic development; incorrect assessment of the rural community’s role as a phenomenon immanently inherent to the Russian society; monarchy that turned out to be weak-willed and demoralized in the conditions prosperity of education, culture and social expectations of the population. Before the revolution, the political spectrum of the parties, in spite of it diversity, was clearly biased toward the influence of socialdemocratic ideas. Lenin's revolutionary flair had affected the situation decisively.